Efeitos da interação social na taxa de desconto do atraso em escolhas monetárias intertemporais - Sampaio, Waldir Monteiro (Universidade Federal de São Carlos, 2019)
Research on intertemporal choices has traditionally been conducted with participants in individual experimental sessions. This is a research that sought to subvert this pattern by producing experimental data on delay discount rates in collective intertemporal choices, understanding the role of social interaction. For this, a study was conducted with two groups, whose difference consisted only in the order of application of the tests, being individual-collective in group One and collective-individual in group Two. The data allowed comparing the pattern of choices between groups and applications and the effect of the order of performance of collective and individual tests. The results showed that participants who answered the test individually after the collective test (group two) had a higher discount rate than those who answered the individual test first (group one). However, no significant differences were found between the rates in the individual and collective applications of the test. The results suggest that while collective and individual achievements maintain the same response pattern, the experience of making this type of choice collectively may increase the future individual choice discount rate. The results are controversial considering previous literature that suggests significant differences in collective and individual discount rates.
Effects of social interaction on delay discounting rate on intertemporal monetary choices
Keywords: Desconto do atraso; Interação social; Escolhas intertemporais; Delay discounting; Social interaction; Intertemporal choices; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS COGNITIVOS E ATENCIONAIS